2021
DOI: 10.3390/ijerph18030926
|View full text |Cite
|
Sign up to set email alerts
|

Regional Strain Pattern Index—A Novel Technique to Predict CRT Response

Abstract: Background: Cardiac resynchronization therapy (CRT) improves outcome in patients with heart failure (HF) however approximately 30% of patients still remain non-responsive. We propose a novel index—Regional Strain Pattern Index (RSPI)—to prospectively evaluate response to CRT. Methods: Echocardiography was performed in 49 patients with HF (66.5 ± 10 years, LVEF 24.9 ± 6.4%, QRS width 173.1 ± 19.1 ms) two times: before CRT implantation and 15 ± 7 months after. At baseline, dyssynchrony was assessed including RSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Park et al (17) were the first who developed a risk score, the EchoCG score, by using echocardiographic strain analysis to predict the reverse remodeling after CRT implantation. Strain analysis was included in many models later (11,(18)(19)(20). Similarly, to strain analysis, electrophysiologic modalities were also used in risk score development, such as sophisticated ECG analysis (21)(22)(23), vectorcardiography (24), or heart rate histogram analysis (25).…”
Section: Zonimentioning
confidence: 99%
“…Park et al (17) were the first who developed a risk score, the EchoCG score, by using echocardiographic strain analysis to predict the reverse remodeling after CRT implantation. Strain analysis was included in many models later (11,(18)(19)(20). Similarly, to strain analysis, electrophysiologic modalities were also used in risk score development, such as sophisticated ECG analysis (21)(22)(23), vectorcardiography (24), or heart rate histogram analysis (25).…”
Section: Zonimentioning
confidence: 99%
“…Some studies have shown that the ventricular MD assessment using transthoracic echocardiography (TTE), magnetic resonance imaging (MRI), computed tomography (CT), and single-photon emission computed tomography (SPECT) can play a key role in the prediction of CRT response [ 15 , 16 , 17 , 18 , 19 ]. However, according to other studies, TTE indicators are not reliable CRT response predictors [ 20 ].…”
Section: Introductionmentioning
confidence: 99%